Gene cloning and expression of fatty acid-binding protein from grass carps (Ctenopharyngodon idellus) in Escherichia coli - CHEN Li-xiang; ZOU Zeng-ding; SU Jian-ming; ZHANG Huai-yun; XIAO Tiao-yi (浙江大学学报. 农业与生命科学版, 2008)
A pair of primers were designed based on the conservative sequences of FABP gene of other species published in the GenBank, and the FABP gene was amplified using grass carp (Ctenopharyngodon idellus) cDNA library as templates. Then the FABP gene was directionally cloned into expression vector pET32A to construct pET32A-FABP recombinant. This recombinant was transformed into Escherichia coli BL21 (DE3). After induction by IPTG, an expected 33 kDa protein was found by SDS-PAGE analysis, accounting for 49.5% of total soluble protein. The result lays helpful foundation for understanding the biological function of fatty acid-binding protein and effects of FABP gene on fatty acid metabolism.